Ragam Ornamen Atap Klenteng Jin De Yuan sebagai Salah Satu Aset di Kawasan Kota Tua - Salim, Polniwati (Humaniora, 2011)
The Plurality of cultures in the country of Indonesia can be seen from the diverse ethnics and tribal minorities and the majorities either. The numbers of Klenteng/temple as one of the places of worship of minority Chinese community which has now been given freedom by the government of Indonesia, are still very few. Jin De Yuan Klenteng is one of the mainstay of tourism in the Area Chinatown, Glodok who entered the Old City area in the world. Therefore, the aesthetic value in the pagoda is very important to be raised in order to remain attractive as a tourism asset. How the application of aesthetic elements on the exterior of Jin De Yuan temple, and any decoration is used, by looking at the positive side of social relationships and cultural preservation, is the  point that must be noticed and developed by all of us.